Republic of Moldova : Poverty Reduction Strategy Paper-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2013)
This Joint Staff Advisory Note focuses on Republic Of Moldova's Poverty Reduction Strategy Paper and National Development Strategy (NDS). The NDS unifies in one document the government's poverty reduction strategy and development vision. The NDS argues that Moldova needs to add productivity-enhancing investment and exports as growth drivers to its traditional consumption-based growth model. The strong pace of growth observed in the mid-2000s was driven by domestic consumption fuelled by remittances. The NDS calls for a shift from the current consumption-based growth model toward one based on raising investments, increasing productivity and competitiveness, developing export industries, and promoting a knowledge-based society.